Description of five new and six known species of the genus Basirotyleptus Jairajpuri, 1964 (Nematoda: Dorylaimida: Tylencholaimoidea) from the Western Ghats, India - Islam, Md Niraul; Ahmad, Wasim (European Journal of Taxonomy, 2022)
Five new and six known species belonging to the genus Basirotyleptus collected from the Western Ghats, India, are described and illustrated. Basirotyleptus conicaudatus sp. nov. is characterized by having 0.42–0.44 mm long body; odontostyle 9.5–10.0 μm, odontophore 11.5–12.0 μm; pharyngeal bulb pear-shaped, 14–15% of total neck length; female genital system mono-opisthodelphic; tail conoid with acute terminus. Basirotyleptus constrictus sp. nov. is characterized by having 0.38–0.49 mm long body; perioral disc distinct; odontostyle 9–10 μm, odontophore 14–15 μm; pharyngeal bulb pear-shaped, 15–17% of total neck length; female genital system mono-opisthodelphic; tail rounded to conoid. Basirotyleptus goaensis sp. nov. is characterized by having 0.73–0.87 mm long body; odontostyle 13.0–14.5 μm, odontophore 15.0–17.5 μm; pharyngeal bulb pyriform, 16–18% of total neck length; female genital system mono-opisthodelphic; tail rounded. Basirotyleptus neocaudatus sp. nov. is characterized by having 0.31–0.44 mm long body; odontostyle 7.5–9.5 μm, odontophore 10–13 μm; pharyngeal bulb pear-shaped, 14–19% of total neck length; female genital system mono-opisthodelphic; tail conoid with acute terminus. Basirotyleptus siddiqii sp. nov. is characterized by having 0.36 mm long body; odontostyle 7.5–8.0 μm, odontophore 10.0–10.5 μm; pharyngeal bulb pear-shaped, 15–16% of total neck length; female genital system mono-opisthodelphic; tail conoid. Six known species viz., B. basiri, B. pini, B. nindei, B. ethiopicus, B. acus, B. minutus are also described and illustrated. Along with light microscopic study, line drawings, compendium and key to species of Basirotyleptus are also provided.